Record of solar activity in southeast Michigan across a one year period between 2023-2024 - Avramenko, Aleksandr (Ecological Questions, 2025)
The Detroit area is situated in a unique ecological region, with the Great Lakes holding the largest freshwater supply on the Planet. Moreover, it plays a crucial role in the United States’ economy. Therefore, studies focusing on the ecological status of the region are warranted. This manuscript records the visible spectra, temperature, luminous flux, and relative humidity in the Detroit area over a one-year period. The data show a relatively stable spectrum during the noon hours, as well as that the temperature appears to drop below freezing only for one month (January). The consequences of these results and their impact on the area are discussed throughout the manuscript. Moreover, the luminous flux and temperature changes observed during the April 8th 2024, eclipse are reported.